Implementasi Relaksasi Nafas Dalam Pada Asuhan Keperawatan Pasien Gastritis Dengan Gangguan Nyeri Akut Untuk Mengurangi Skala Nyeri - Tiara Wyanda; Rinawati Tarigan (STIKES Columbia Asia Medan, 2025)
Background : Gastritis, an inflammation of the gastric mucosa, is a common health problem that often causes acute pain. This study aims to determine the effectiveness of deep breathing relaxation techniques as a non-pharmacological treatment intervention in reducing pain levels in ulcer patients. Using a case study method, deep breathing relaxation therapy was administered for 5-10 minutes using the technique of inhaling through the nose, holding for 3 seconds, and slowly exhaling through the mouth. Results of observations over 5 days showed a decrease in pain levels in patients. This study concluded that deep breathing relaxation therapy is effective in reducing pain in ulcer patients and recommended its implementation to improve patient knowledge and experience in pain management.